Effectiveness of interventions in preventing disorganized attachment: A meta-analysis. (11th April 2017) - Facompré, Christopher R.; Bernard, Kristin; Waters, Theodore E. A.
Abstract: Disorganized attachment is associated with a host of negative developmental outcomes, leading to a growing interest in preventative interventions targeting the attachment relationship in infancy. The objective of this meta-analysis was to assess the effectiveness of interventions that aimed to prevent or reduce rates of disorganization among children at risk. We performed a literature search using PsycINFO, MEDLINE, and ProQuest databases for studies published between January 1989 and August 2016. All 16 studies ( N = 1, 360) included a control condition and reported postintervention rates of organized and disorganized attachments assessed by the Strange Situation Procedure. Results showed that, overall, interventions were effective in increasing rates of organized attachment compared to control conditions ( d = 0.35, 95% CI [0.10–0.61]). Moderator analyses demonstrated that interventions were more effective (a) in more recently published studies than in older studies, (b) for maltreated samples than nonmaltreated samples, and (c) as children increased in age. These results have important implications for future development, tailoring, and implementation of attachment-based intervention programs.